2020
DOI: 10.1002/hep.30979
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of Noninvasive Screening for Alcohol‐Related Liver Fibrosis

Abstract: on behalf of the GALAXY ConsortiumBaCKgRoUND aND aIMS: Alcohol-related liver disease is often undetected until irreversible late-stage decompensated disease manifests. Consequently, there is an unmet need for effective and economically reasonable pathways to screen for advanced alcohol-related fibrosis. appRoaCH aND ReSUltS: We used real-world data from a large biopsy-controlled study of excessive drinkers recruited from primary and secondary care, to evaluate the cost-effectiveness of four primary care initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 29 publications
(32 reference statements)
0
43
0
Order By: Relevance
“…A cost-effectiveness analysis evaluating screening methods for alcohol-related liver fibrosis demonstrated that direct liver stiffness measurement via transient elastography is a highly cost-effective procedure, with 93 % accuracy and incremental cost-effectiveness ratios of $ 490 to $ 1,037 per quality-adjusted life-year in high-prevalence populations 23 . Nonetheless, there is a lack of studies evaluating the cost-effectiveness of EUS in the diagnostic workup of chronic liver disease, and its implications given the additional features found during EUS evaluation of patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…A cost-effectiveness analysis evaluating screening methods for alcohol-related liver fibrosis demonstrated that direct liver stiffness measurement via transient elastography is a highly cost-effective procedure, with 93 % accuracy and incremental cost-effectiveness ratios of $ 490 to $ 1,037 per quality-adjusted life-year in high-prevalence populations 23 . Nonetheless, there is a lack of studies evaluating the cost-effectiveness of EUS in the diagnostic workup of chronic liver disease, and its implications given the additional features found during EUS evaluation of patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these biomarkers (in particular, the ELF test) are highly cost-effective and should be tested in primary health care settings. 37,38 Lastly, advanced fibrosis can be ruled out in primary health care patients with an ELF value <10.5 or an FT < 0.58. 32 Therefore, these tests might be helpful in reducing the need for liver biopsy.…”
Section: Biological Testsmentioning
confidence: 99%
“…Although patented biomarkers are considered to have lower applicability compared with nonpatented ones given their higher cost, two recent studies 37,38 have found that the ELF score is cost-effective in primary health care 38…”
Section: Use In Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations